La gradabilité nominale en anglais et en français - Pauline Haas; Anne Jugnet (Anglophonia)
The aim of this paper is to describe the gradability of nouns in French and in English. After a description of different conceptions of nominal gradability in the literature, we provide our definition of lexical gradability. Three classes of nouns can be gradable : stative intensive nouns (cleverness / intelligence), evaluative nouns (idiot / idiot), and dynamic intensive nouns (modernization / modernisation). The comparison between French and English shows that, even though a few discrepancies can be highlighted, nominal gradability is mostly similar in both languages.